Can one tweet affect the global automotive industry? - Hahn, Simon Markus Lukas (2017)
Social Media has become a powerful tool and is the main communication tool used by the newly elected President of the United States, Donald Trump. So far, this is unexplored territory in the world of finance and no event studies have been applied to a tweet by an influential person. Therefore, this work should give an impulse to the discussion about social media use and its consequences. While President Trump is known for his unorthodox way to share his opinion and thoughts with the world, the consequences for firms, industries and whole economies have not been studied. The car industry is very cost sensitive and therefore reactions towards regulatory changes should be measurable in case a certain level of credibility is guaranteed. When Mr. Trump tweeted that imported cars should be taxed at 35 percent, German car producers’ share prices reportedly decreased by 1 to 2 percent. While these manufacturers were addressed directly, this study proves that not only German companies but the entire global automotive industry was negatively affected by the statement. I found average abnormal returns of -0,5 percent to -1,4 percent for up to three days following the event, depending on the applied estimation windows. The tweet seems to have caused the largest change in share prices for smaller firms such as suppliers. My findings show that the use of social media can affect an entire industry, if used by influential people.